Dual targeting of cancer-related human matrix metalloproteinases and carbonic anhydrases by chiral N-(biarylsulfonyl)-phosphonic acids. (1st January 2017) - Luisi, Grazia; Angelini, Guido; Gasbarri, Carla; Laghezza, Antonio; Agamennone, Mariangela; Loiodice, Fulvio; Supuran, Claudiu T.; Campestre, Cristina; Tortorella, Paolo
Abstract: A series of nanomolar phosphonate matrix metalloproteinase (MPP) inhibitors was tested for inhibitory activity against a panel of selected human carbonic anhydrase (CA, EC 4.2.1.1) isozymes, covering the cancer-associated CA IX and XII. None of the reported sulfonyl and sulfonylamino-derivatives sensitively affected the catalytic activity of the cytosolic isoforms CA I and II, which are considered off-target isoforms in view of their physiological role. The most active inhibitors were in the series of chiral N -(sulfonyl)phosphovaline derivatives, which showed good to excellent inhibitory activity over target CAs, with compound15 presenting the best isoform-selectivity toward CA IX. We suggest here that the phosphonates have the potential as dual inhibitors of MMPs and CAs, both involved in tumor formation, invasion and metastasis.